Measurements of Volatile Organic Compounds During the COVID‐19 Lockdown in Changzhou, China. Issue 20 (15th October 2021) - Jensen, Andrew; Liu, Zhiqiang; Tan, Wen; Dix, Barbara; Chen, Tianshu; Koss, Abigail; Zhu, Liang; Li, Li; de Gouw, Joost
Abstract: The COVID‐19 outbreak in 2020 prompted strict lockdowns, reduced human activity, and reduced emissions of air pollutants. We measured volatile organic compounds (VOCs) using a proton‐transfer‐reaction mass spectrometry instrument in Changzhou, China from 8 January through 27 March, including periods of pre‐lockdown, strict measures (level 1), and more relaxed measures (level 2). We analyze the data using positive matrix factorization and resolve four factors: textile industrial emissions (62 ± 10% average reduction during level 1 relative to pre‐lockdown), pharmaceutical industrial emissions (40 ± 20%), traffic emissions (71 ± 10%), and secondary chemistry (20 ± 20%). The two industrial sources showed different responses to the lockdown, so emissions from the industrial sector should not be scaled uniformly. The quantified changes in VOCs due to the lockdowns constrain emission inventories and inform chemistry‐transport models, particularly for sectors where activity data are sparse, as the effects of lockdowns on air quality are explored. Plain Language Summary: In response to the outbreak of COVID‐19 in early 2020 and in the interest of public health, many countries enacted lockdowns. Restrictions on non‐essential travel and work resulted in reductions in air pollutant emissions. Concentrations of organic air pollutants were measured in Changzhou, China before and during the lockdowns. These pollutants were then grouped together based on their behavior in time and chemical signatures, and these groups were assigned to emission sources such as motor vehicles and industries. Motor vehicle pollutant emissions were reduced by 70% during the lockdown while textile and pharmaceutical industrial emissions were reduced by 40% and 60%, respectively. Different kinds of industries, such as those that are essential versus non‐essential during a global pandemic, responded differently to the lockdown, so industries should not be treated as a single entity. These results inform further studies by providing details on the effect of lockdown on emission sources. Key Points: We measured and quantified volatile organic compounds (VOCs) in Changzhou, China during the COVID‐19 lockdowns Traffic‐related VOC emissions were reduced by 70%, which agrees with reductions in traffic counts Textile and pharmaceutical industry VOC emissions responded differently, so industrial emissions should not be scaled uniformly